FROM STAGE TO SCREEN: APPLYING SEMIOTIC COMEDY IN MODERN ENTERTAINMENT FORMATS - Горбатий, Олександр (SWorldJournal, 2025)
The article focuses on analyzing the transformation of semiotic humor in the context of its transition from theatrical performance to screen-based forms of contemporary entertainment. The aim of the study is to examine how the use of semiotic humor has ev